How Phosphorus Fertilization Alleviates the Effect of Salinity on Sugar Beet (Beta vulgaris L.) Productivity and Quality - Hamza Bouras; Ahmed Bouaziz; Bassou Bouazzama; Abdelaziz Hirich; Redouane Choukr-Allah (Agronomy, 2021)
Salinity is a major problem affecting agriculture in many regions of the world, including Morocco. The best agronomic practices such as fertilization are used to cope with salinity stress and improve productivity under saline conditions. The objective of this study is to evaluate the interactive effect of phosphorus and salinity on sugar beet (Beta vulgaris L.) cv. “Sporta” productivity and quality. A field experiment was carried out, testing three levels of irrigation water salinity (ECw = 0.7; 4, 8, and 12 dS·m−1) and three levels of phosphorus (100, 120, and 140 kg P2O5·ha−1) organized in a split-plot design with three replicates. This research was conducted in the Tadla region (center of Morocco) during two seasons in 2019 and 2020. The obtained results show that irrigation water salinity had a negative effect on most growth and productivity parameters. For instance, sugar beet yield reduced by 21% and by 26% under saline irrigation, with an EC value equal to 4 and 8 dS·m−1, respectively, compared to the control during the 2018–2019 season, and by 1%, 19%, and 27% under saline irrigation, with an EC value equal to 4 and 8 and 12 dS·m−1, respectively compared to the control (0.7 dS·m−1) during the 2019–2020 season. Total sugar content was significantly increased by 5% and 7%, respectively, under saline irrigation, with an EC value of 4 and 8 dS·m−1, respectively, as compared with the control in the first growing season in 2018–2019. However, in the second growing season (2019–2020), only the highest level of saline water (EC = 12 dS·m−1) significantly increased in sugar content by 15% compared to the control. Regarding the P fertilization effect, it was found that a P rate of 120 kg P2O5·ha−1 was enough to improve the yield and sugar content of sugar beet under the tested salinity levels. Thus, P fertilization could be one of the best practices to enhance sugar beets’ tolerance of salinity. To obtain a maximum root and sugar yield under saline water, it is recommended to apply a phosphorus dose of 120 kg P2O5·ha−1.